CRYPTOSPORIDIOSIS PARU DI PENDERITA TBC - R. Heru Prasetyo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
The pulmonary cryptosporidiosis cases had been reported for immunocompromised persons, most all of whom were secunder infected with HIV and AIDS patients. Tuberculosis is a chronic respiratory disease and tending to cause a weakened immune system (immunocompromised). However, pulmonary cryptosporidiosis has not been previously reported as secunder infection in tuberculosis patients. The objective of this study was to know the prevalence of pulmonary cryptosporidiosis determination in tuberculosis patients. This research was carried out by a cross sectional study utilitzing waste sputum samples from tuberculosis patients. The detection of Cryptosporidium oocyst used modified version acid fast stain of Ziehl Neelsen technique. Three sputum samples among 44 sputum samples (6.8%) had Cryptosporidium oocyst positive. These findings suggest that there was a potential for respiratory transmission of cryptosporidiosis. Although the prevalence of pulmonary cryptosporidiosis in tuberculosis patients are low, the researcher suggest that the possibility of pulmonary cryptosporidiosis as a secondary infection in tuberculosis patients existed, and there for a laboratory examination of pulmonary cryptosporidiosis becoming routinely laboratory for tuberculosis patients.